Optimizing efficiency and safety in external beam radiotherapy using automated plan check (APC) tool and six sigma methodology. Issue 8 (19th August 2019) - Liu, Shi; Bush, Karl K.; Bertini, Julian; Fu, Yabo; Lewis, Jonathan M.; Pham, Daniel J.; Yang, Yong; Niedermayr, Thomas R.; Skinner, Lawrie; Xing, Lei; Beadle, Beth M.; Hsu, Annie; et al.
Abstract: Purpose: To develop and implement an automated plan check (APC) tool using a Six Sigma methodology with the aim of improving safety and efficiency in external beam radiotherapy. Methods: The Six Sigma define‐measure‐analyze‐improve‐control (DMAIC) framework was used by measuring defects stemming from treatment planning that were reported to the departmental incidence learning system (ILS). The common error pathways observed in the reported data were combined with our departmental physics plan check list, and AAPM TG‐275 identified items. Prioritized by risk priority number (RPN) and severity values, the check items were added to the APC tool developed using Varian Eclipse Scripting Application Programming Interface (ESAPI). At 9 months post‐APC implementation, the tool encompassed 89 check items, and its effectiveness was evaluated by comparing RPN values and rates of reported errors. To test the efficiency gains, physics plan check time and reported error rate were prospectively compared for 20 treatment plans. Results: The APC tool was successfully implemented for external beam plan checking. FMEA RPN ranking re‐evaluation at 9 months post‐APC demonstrated a statistically significant average decrease in RPN values from 129.2 to 83.7 ( P  < .05). After the introduction of APC, the average frequency of reported treatment‐planning errors was reduced from 16.1% to 4.1%. For high‐severity errors, the reduction was 82.7% for prescription/plan mismatches and 84.4% for incorrect shift note. The process shifted from 4σ to 5σ quality for isocenter‐shift errors. The efficiency study showed a statistically significant decrease in plan check time (10.1 ± 7.3 min, P  = .005) and decrease in errors propagating to physics plan check (80%). Conclusions: Incorporation of APC tool has significantly reduced the error rate. The DMAIC framework can provide an iterative and robust workflow to improve the efficiency and quality of treatment planning procedure enabling a safer radiotherapy process.